Trend Analysis of Monthly and Annual Average Temperatures in Cizre District (Şırnak) (1963-2021) - Avci, Vedat (Fırat University, 2023)
In this study, it is aimed to analyze the trend in average monthly and yearly temperatures in Cizre District. In the study, trends (positive or negative) in monthly and annual average temperatures have been determined, using 59 years of temperature data covering between 1963-2021 from Meteorology Station of the Cizre district. The reason of choosing Cizre as the study area is that it is one of the districts with highest average temperatures in Türkiye and to find out the effects of climate change in the area. In this study, Mann-Kendall Trend Test and Linear Trend Model analysis methods, which are commonly preferred in trend analyses, have been used. Trends in temperatures have been determined by Mann-Kendall method and future predictions were made by Linear Trend method. According to the results, it has been determined that there has been a positive trend in average temperatures in February, April, May, June, July, August, September, October, December and in annual average temperatures in Cizre. Positive trends are more common in spring and summer seasons. This positive trend in temperature average will certainly cause unfavorable impacts on many areas such as agriculture, animal husbandry, and tourism and energy generation. It is advised to initiate necessary studies to reduce the effects of climate change by utilizing water resources consciously.

Bu çalışmada Cizre ilçesinde aylık ve yıllık ortalama sıcaklıklarda yaşanan eğilimlerin analiz edilmesi amaçlanmıştır. Çalışmada Cizre ilçesi Meteoroloji istasyonunun 1963-2021 yılları arasını kapsayan 59 yıllık sıcaklık verileri kullanılarak aylık ve yıllık ortalama sıcaklıklarda eğilimler (pozitif ya da negatif) belirlenmiştir. Cizre’nin çalışma alanı olarak belirlenmesinin nedeni Türkiye’de ortalama sıcaklıkların en yüksek olduğu alanlardan biri olması ve bu alanda iklim değişikliğinin etkilerinin ortaya konulmasıdır. Bu çalışmada eğilim analizlerinde yaygın olarak tercih edilen Mann-Kendall Trend Test ve Linear Trend Model analiz yöntemleri kullanılmıştır. Sıcaklıklardaki eğilimler Mann-Kendall yöntemi ile belirlenmiş, geleceğe yönelik tahminler Linear Trend yöntemi ile yapılmıştır. Bulgulara göre Cizre’de; Şubat, Nisan, Mayıs, Haziran, Temmuz, Ağustos, Eylül, Ekim ve Aralık ayı ortalama sıcaklıkları ile yıllık ortalama sıcaklıklarda pozitif yönde bir eğilimin olduğu belirlenmiştir. Pozitif yönlü eğilimler ilkbahar ve yaz mevsiminde belirgindir. Sıcaklık ortalamalarında tespit edilen pozitif yönlü bu eğilimin tarım, hayvancılık, turizm ve enerji üretimi gibi birçok alanda olumsuz sonuçları olacaktır. İklim değişikliğinin olumsuz etkilerini azaltmak için su kaynaklarının bilinçli kullanımı ile ilgili gerekli çalışmaların yapılması tavsiye edilmektedir.
CİZRE’DE (ŞIRNAK) AYLIK VE YILLIK ORTALAMA SICAKLIKLARIN EĞİLİM ANALİZİ (1963-2021)
Keywords: Environmental Management (Other); Çevre Yönetimi (Diğer); Climate Change Impacts and Adaptation (Other); İklim Değişikliği Etkileri ve Uyarlama (Diğer)